Liquid immersion cooling with enhanced Al2O3 nanofluid for large-format prismatic battery pack: Numerical and statistical investigation - Yousefi, Elnaz; Talele, Virendra; Moralı, Uğur; Mishra, Dhananjay; D., Ramasamy; K., Kadirgama; Najafi Khaboshan, Hasan; Kanthale, Sarthak; Panchal, Satyam (Springer, 2025)
The widespread adoption of lithium-ion batteries (LIBs) owes much to the surging demand for electric vehicles, driven by their advantageous traits such as compact size, low resistance, high power density, and minimal self-discharge rates. Effective temperature control is paramount to guarantee the reliability of LIBs, especially for high-voltage prismatic battery packs, which are susceptible to thermal runaway incidents due to the large amount of heat production. This study examines the use of advanced nanoenhanced fluid immersion cooling for large-format prismatic shape battery packs used in heavy-duty applications. The study compares two cooling configurations: (1) axial fluid flow (z-axis in line flow direction, front face A is the first contact) and (2) battery side axial flow (x-axis in line flow direction, face B is the first contact). The goal is to regulate the temperature of the battery within the optimal range of 25–45 °C, with a maximum threshold of 55 °C, by using a minimum mass flow and pumping power requirement. The assessment of optimal thermal design is conducted using numerical and physics-guided statistical analysis, taking into account factors such as ambient temperature, C-rates, and nanoparticle volume percentage. Supporting numerical simulations and physics-guided statistical findings indicate that the temperature at which a battery operates and the rate at which it is charged have a substantial influence on the temperature of the battery pack.